The predictive value of changes in 18F-FDG PET/CT cardiac uptake patterns and metabolic parameters for anthracycline based chemotherapy induced cardiac toxicity in lymphoma patients - Runlong Lin; Aijuan Tian; Ying Wang; Xiaomei Wang; Xin Yuan; Jing Yu; Guihua Li; Wenli Xie (PLoS ONE, 2025)
Objective This study aims to examine alterations in positron emission tomography with 2-deoxy-2-[fluorine-18]fluoro-D-glucose integrated with computed tomography (18F-FDG PET/CT) heart uptake patterns and metabolic factors before and after anthracycline-based chemotherapy in lymphoma patients, and to investigate the added benefit of oncological 18F-FDG PET/CT in chemotherapy-induced heart damage. Materials and Methods Between July 2017 and December 2022, lymphoma patients diagnosed at the Second Affiliated Hospital of Dalian Medical University who underwent 6 cycles of anthracycline-based chemotherapy and had baseline and 6-cycle oncological 18F-FDG PET/CT scans were included. A total of 366 patients with complete data sets were enrolled. Relevant parameters including blood tests, lipid profile, cardiac biomarkers, lactate dehydrogenase (LDH), erythrocyte sedimentation rate (ESR), albumin (ALB), β2-microglobulin (β2-MG), and cardiac ultrasound findings were collected. Patients were monitored from the initiation of chemotherapy until January 2024, and the occurrence of cancer therapy-related cardiovascular toxicity (CTR-CVT) was documented. Changes in PET/CT heart uptake patterns pre- and post-treatment, along with the presence or absence of CTR-CVT, were used to analyze alterations in left ventricular and epicardial adipose tissue metabolic parameters, as well as changes in echocardiographic parameters. Logistic regression analysis was employed to identify risk factors for CTR-CVT. Results Among lymphoma patients who received 6 cycles of anthracycline-based chemotherapy, compared to their initial state, there was a notable decrease in white blood cell count (WBC), neutrophil-to-lymphocyte ratio (NLR), erythrocyte sedimentation rate (ESR), and β2-microglobulin (β2-MG) levels post-treatment. Conversely, albumin (ALB) levels and blood lipid levels significantly rose after treatment. Post-treatment, the maximum standardized uptake value (SUVmax) and mean standardized uptake value (SUVmean) of the left ventricle significantly increased, and the percentage of patients exhibiting no uptake pattern in the left ventricle significantly decreased, while those with diffuse uptake pattern notably increased. Moreover, the count of patients with abnormal cardiac uptake significantly rose post-treatment. Analyzing changes in uptake patterns, the group displaying abnormal changes exhibited an increase in left atrial diameter and a decrease in left ventricular ejection fraction compared to the group with normal changes. The SUVmax of the epicardial adipose tissue was notably higher in the abnormal change group compared to the normal change group. Based on the presence or absence of CTR-CVT, the CTR-CVT group showcased higher left atrial diameter and left ventricular end-systolic diameter, and lower left ventricular ejection fraction compared to the non-CTR-CVT group. Additionally, the SUVmax and SUVmean of the epicardial adipose tissue were higher in the CTR-CVT group than in the non-CTR-CVT group. Left atrial end-systolic diameter, left ventricular ejection fraction, SUVmax of the epicardial adipose tissue, and change in uptake pattern were identified as risk factors for CTR-CVT. Conclusion In lymphoma patients treated with anthracycline-based chemotherapy, alterations in 18F-FDG PET/CT cardiac uptake patterns and metabolic parameters observed during the follow-up period before and after treatment, as well as changes in epicardial adipose tissue metabolic parameters post-treatment, could serve as predictors for the occurrence of CTR-CVT.